Who Leaves? The Outmigration of the Foreign-Born - Borjas, George J.; Bratsberg, Bernt (The Review of Economics and Statistics, 1996)
This paper analyzes the return migration of foreign-born persons in the United States.We argue that return migration may have been planned as part of an optimal life cycle residential location sequence.Return migration also occurs because immigrants based their initial migration decision on erroneous information about opportunities in the United States.The study uses the 1980 Census and administrative data from the immigration and Naturalization Service.Immigrants tend to return to wealthy countries which are not too far from the United States.Moreover, return migration accentuates the type of selection characterizing the immigrant population left in the United States.